Publication bias in measuring intertemporal substitution - Tomáš Havránek (Charles University in Prague, Institute of Economic Studies (IES), 2013)
I examine 2,735 estimates of the elasticity of intertemporal substitution in consumption (EIS) reported in 169 published studies. The literature shows strong publication bias: researchers report negative and insignificant estimates less often than they should, which pulls the mean estimate up by about 0.5. When I correct the mean for the bias, for macro estimates I get zero, even though the reported t - statistics are on average two. The corrected mean of micro estimates for asset holders is around 0.3-0.4. Calibrations of the EIS greater than 0.8 are inconsistent with the bulk of the empirical evidence.
Keywords: E21; C83; 330; Elasticity of intertemporal substitution; consumption; publication bias; meta-analysis